Implementasi kurikulum berbasis Tarbiyatul Muallimin Al Islamiyah dalam meningkatkan kualitas dan kapabilitas santri di Pondok Pesantren - Cahyono, Gangsar; Aljauhari, Shofwan; Yulia Rahman, Hendra (Al-Ishlah: Jurnal Pendidikan Islam, 2023)
The implementation of the curriculum based on the values of Tarbiyatul Muallimin Al Islamiyah at Annajah Yamra Merauke Islamic boarding school by emphasizing the integration of the daily attitudes and behavior of students can run well as the vision and mission of education. However, this context tends to be neglected in scientific discussions. The study in addition to complementing the shortcomings of the studies that have been done, also focuses on the question "How are the processes and methods of implementing a curriculum based on the values of Tarbiyatul Muallimin Al Islamiyah applied at the Annajah Yamra Merauke boarding school?" To answer this question, this study uses a descriptive qualitative approach by conducting structured observations and interviews with leaders and teachers at the Annajah Yamra Merauke boarding school. The findings in this study show that in the process of curriculum implementation in faith-based schools, an extensive communication process is a very important context to do. In other words, success in implementing an educational curriculum is not only done through a communicative process, but also involves all elements in the context of applying a curriculum collectively. This context is what pesantren Annajah Yamra Merauke does in implementing a curriculum based on the values of Tarbiyatul Muallimin Al Islamiyah.